Neisseria gonorrhoeae antimicrobial resistance in Spain: a prospective multicentre study. (11th February 2021) - Salmerón, Paula; Viñado, Belén; Arando, Maider; Alcoceba, Eva; Romero, Beatriz; Menéndez, Blanca; Bernal, Samuel; Idigoras, Pedro; Colomina, Javier; Martin-Saco, Gloria; Leal-Negredo, Álvaro; Torreblanca, Aurora; et al.
Abstract: Objectives: Gonococcal infection is one of the most reported sexually transmitted infections and antimicrobial resistance in Neisseria gonorrhoeae (NG) is challenging for the treatment of this infection. This observational study aimed to describe antimicrobial resistance of NG and epidemiological data from patients with gonococcal infection in eight regions of Spain, for updating the local therapeutic guidelines. Methods: MICs of penicillin, cefixime, ceftriaxone, azithromycin, ciprofloxacin, fosfomycin and gentamicin were determined by Etest for all NG isolates recovered from 1 April 2018 to 30 September 2019 from 10 hospitals in Spain. Resistance determinants were identified using logistic regression analysis. Differences with a P value <0.05 were considered statistically significant. Results: Antimicrobial susceptibility testing was performed for 2571 gonococci isolated from 2429 patients. 44.5% (945/2124) of patients were MSM. The resistance rate to extended-spectrum cephalosporins was low, with 0.2% (6/2561) of isolates resistant to ceftriaxone and 1.7% (44/2517) of isolates resistant to cefixime. The overall azithromycin resistance rate was 12.1% (310/2560), but differed greatly depending on the area. 56.2% (1366/2429) of the strains studied were ciprofloxacin resistant. MIC50 and MIC90 values of gentamicin and fosfomycin were 4 and 8 mg/L and 24 and 48 mg/L, respectively. Conclusions: Our study shows that NG susceptibility to extended-spectrum cephalosporins remains high in Spain. The azithromycin resistance rate questions the suitability of dual therapy. This study provides data of interest for updating the national treatment guidelines and highlights the need to develop and implement a national sentinel gonococcal antimicrobial susceptibility programme.